The process mediation framework for semantic web services. (6th February 2009) - Vaculin, Roman; Neruda, Roman; Sycara, Katia
The ability to deal with the incompatibilities of service requesters and providers is a critical factor for achieving interoperability in dynamic open environments. We focus on the problem of process mediation of the semantically annotated process models of the service requester and service provider. We propose an Abstract Process Mediation Framework (APMF) identifying the key functional areas that need to be addressed by process mediation components. Next, we present algorithms for solving the process mediation problem in two scenarios: (1) when the mediation process has complete visibility of the process model of the service provider and service requester (complete visibility scenario) and (2) when the mediation process has visibility only of the process model of the service provider, but not the service requester (asymmetric scenario). The algorithms combine planning and semantic reasoning with the discovery of appropriate external services such as data mediators. Finally, the Process Mediation Agent (PMA) is introduced, which realises an execution infrastructure for runtime mediation.